Shields dropped - Németh, György (Acta Classica Universitatis Scientiarum Debreceniensis, 2026)
Ancient sources regarded throwing away one’s shield as a punishable crime in Greek poleis, and their testimony has been accepted by modern scholarship. However, if we read the accounts of actual instances of shield-dropping, we find that the interests of the whole community often took precedence over the demand to penalize shield-droppers.